(3fUjMI Gdedhcs - (3GdZRGdi , CHh MGeO eMeO Hf eMeO Hf eMeOs; (3GdZRGdj , MLI GdESdGe CHh MGeO eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3CMeO Hf eMeO GdeGQYi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CfYGeg hCaVGdg hHYO abO SCdfi GdeJbOejf GdCcGHQ Cf Cfbd gPG GdcJGH hgh fUjMI Gdedhc bGd CHh MGeO GYde jG SdWGf GdYGde hedc GdTQb hGdZQH Ef ddg Ydjc fYekG XGgQI s
(3BNQgG (B:s
(3adG JYLdf ai GdLhQ eGOeJ bGOQkG aCNQg CKe hNha hYPGH JfGe heG GdeXdhe Yfc HfGFe hOYhJg MLGH s
(3eJQLeI ef GdaGQSjI Edi GdYQHjIs
(3cJHJ Hbde Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
Keywords: (3GdSjGSI hGdGLJeGYs